Dansk nadverpraksis 2020-21 - Kristensen, Johanne Stubbe Teglbjærg; Enggaard, Nete Helene (Dansk Teologisk Tidsskrift, 2022)
In this article, we describe and analyze the discussion of the celebration of the Lords Supper in the Danish Evangelical Lutheran Church during the pandemic 2020-21. We notice that the Lutheran World Federation as well the Swedish and Norwegian bishops expressed or recommended a no to any attempts at a digital celebration of the Lords Supper. We also emphasize that most Danish pastors were spontaneously careful in their practice and hesitated towards the attempt at a digital celebration. Nonetheless, some Danish bishops seemed to assume that this was possible and their assumption became the beginning of a discussion in a few Danish media, primarily in Kristeligt Dagblad. In the article, we analyze this Danish discussion in the context of the confessional writings of the Danish Evangelical Lutheran Church and argue for a hesitating position that calls for more research. This presupposes that the confessional writings were written in a different, non-digitalized, context, and it takes into account knowledge that already exist on Lutheran understandings of the Lords Supper e.g. in the Book of Concord.